'Learning again and again to pray': Anglican Forms of Daily Prayer, 1979–20141. Issue 1 (16th May 2016) - Burns, Stephen
Abstract: The 2014 publication of the Episcopal Church's resource for daily prayer, Daily Prayer for All Seasons, invites reflection on recent developments in provision for everyday services around the Anglican Communion. Not only is the new resource considerably different from the material it complements in the Book of Common Prayer 1979, it also represents a departure from a certain commonality that has emerged in material from around the Communion since 1979. While this article does not map those developments in detail, it does chart some of the shifts occurring in various provinces and relates that survey to current discussions about 'Anglican identity and liturgical diversity'. The article serves both as an introduction to Daily Prayer for All Seasons and as a wider reflection on Anglican forms of everyday services in the period from 1979–2014.